2002
DOI: 10.1002/1618-2863(20020806)2:8<229::aid-elsc229>3.0.co;2-9
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant Protein Production with Pichia pastoris in Continuous Fermentation – Kinetic Analysis of Growth and Product Formation

Abstract: Continuous fermentation was applied to the production of recombinant human chymotrypsinogen B (hCTRB) by the methylotrophic yeast Pichia pastoris as a tool for the kinetic analysis of growth and product formation. Using methanol as the sole source of carbon, energy, and induction, cell growth could be described by a non‐competitive Monod approach. Maximum growth rate μmax was determined to 0.084 h‐‐1 and the KM‐value for methanol to 0.22 g·L‐‐1, respectively. With respect to product formation, a similar model … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
45
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(48 citation statements)
references
References 11 publications
1
45
0
Order By: Relevance
“…Nevertheless, Ohi et al (1998) reported that after serial cultivation of a P. pastoris strain expressing human serum albumin (two copies) for 83 generations, 0.01% of cells were found to lose the foreign gene. Also, Curvers et al (2002) reported that in continuous cultivation of a recombinant P. pastoris strain expressing recombinant human chymotrypsinogen B (single copy), yeast cells in the bioreactor soon lost the ability to express the protein due to the instability of P. pastoris when the residual methanol exceeded 4 g l -1 .…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, Ohi et al (1998) reported that after serial cultivation of a P. pastoris strain expressing human serum albumin (two copies) for 83 generations, 0.01% of cells were found to lose the foreign gene. Also, Curvers et al (2002) reported that in continuous cultivation of a recombinant P. pastoris strain expressing recombinant human chymotrypsinogen B (single copy), yeast cells in the bioreactor soon lost the ability to express the protein due to the instability of P. pastoris when the residual methanol exceeded 4 g l -1 .…”
Section: Discussionmentioning
confidence: 99%
“…In this study, 100% methanol was used to a final concentration of 0.3-0.5% every 24 h, and the highest expression was made in 0.5% of methanol. Curvers and colleagues' results showed that when methanol concentration increases more than a critical point, a selective pressure will be imposed against product formation leading to the enrichment of nonproducing mutants [36].…”
Section: Discussionmentioning
confidence: 99%
“…Scenarios G1-G10 have been extracted from P. pastoris cultures producing recombinant human chymotrypsinogen B [36]. Scenario H1 corresponds to the continuous fermentation of a P. pastoris strain for the extracellular production of a recombinant ovine interferon protein [37].…”
Section: P Pastoris Experimental Data Setmentioning
confidence: 99%